Towards multilingual competence: examining beliefs and agency in first year university students' language learner biographies. Issue 5 (3rd September 2022) - Pirhonen, Hillamaria
ABSTRACT: As working life across the world is increasingly multilingual, multicultural and multidisciplinary, higher education language teaching is faced with a challenge of how to prepare students for it. Many universities have recently developed multilingual pedagogies but central to their success is learners' perceptions of these practices. To fill this gap, this article explores first year university students' language learner biographies to gain insight into how learners construct their linguistic realities. The biographies were studied with discourse analytical methods to examine the participants' beliefs about language learning and their sense of agency in it. The results reveal that participants tend not to portray themselves as agentive learners but rather position agency as an outside factor affecting their language learning. In addition, the participants' discourses differed in terms of languages, which adds to previous studies noting the complexity of learner beliefs. Understanding these dynamics can help teachers address students' beliefs in the classroom and accordingly support learners to create meaning in their language learning. The findings further suggest that beliefs should be studied from multilingual perspectives also in the future.